A review of the rudderfish genus Tubbia (Stromateoidei: Centrolophidae) with the description of a new species from the Southern Hemisphere - Last, Peter R.; Daley, Ross K.; Duhamel, Guy (Zootaxa, 2013)
A combination of morphological and molecular techniques was used to confirm the existence of a second species of the monotypic centrolophid genus Tubbia. Adults of the seamount rudderfish, T. stewarti sp. nov., which reaches about 56 cm SL, is mesopelagic at depths of 525–1438 m in the temperate waters of the Southern Hemisphere. It has a confirmed dis-tribution off Australia and New Zealand where it occurs sympatrically with the wider ranging T. tasmanica Whitley. Like most other members of the group, juveniles live in the epipelagic zone where they have been taken at 30–50 m depth. The new species has a more robust head, more slender body, more flattened interorbit, longer jaws, denser head pores, rela-tively larger eyes and nostrils, narrower caudal peduncle and more vertebral centra than T. tasmanica, and also differs sub-tly in some morphometric ratios. A rediagnosis of T. tasmanica is also provided.